Earnings Risk and Volatility Relative to Macroeconomic Factors and Corporate Governance - Julio Afiegarlin Wade; Aaliyah Azka Fairuzza; Maylany Eka Maharani; Ricky Candra Hidayyah (Universitas Dinamika, 2026)
Aims - This study aims to synthesise the multidimensional drivers of earnings volatility and evaluate the effectiveness of strategic mitigation mechanisms in the Indonesian capital market. Methodology - A meta synthesis approach was employed, systematically analysing twelve high impact peer reviewed articles published between 2020 and 2024. The data, spanning various indices such as LQ45 and IDX30, were categorised through thematic analysis and predictive synthesis to bridge quantitative financial metrics with qualitative governance frameworks. Findings - The results reveal that while 50% of volatility is driven by internal fundamental fragilities like leverage and asset inefficacy, the most potent buffers are non financial. Governance resilience, characterised by board diversity and virtue based communication, significantly reduces information asymmetry. Moreover, the integration of Sharia principles and technological adaptation serves as a crucial shield against systemic macro-techno shocks. Research Limitations - The study is limited by its geographical focus on Indonesia and a heavy reliance on existing quantitative literature. Theoretically, it implies a shift from purely numerical risk assessments to a holistic resilience model. Practically, it suggests that regulators and firms should prioritise ethical integrity as a strategic tool for market stability. Originality - This research is unique in its integration of Virtue Values and TechnoFinancial Dynamics into a unified predictive risk-mitigation framework, offering a novel perspective on corporate resilience beyond traditional financial ratios.